EKSPLORASI KONSEP-KONSEP ETNOMATEMATIKA PADA RUMAH ADAT “KEDA NUA PU’U NIDA” DESA WATUNGGERE - Siprianus Gheta; Agustina Mei; Agnes Pendy (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
The objectives of this research are 1). to find out a brief history of the Keda Nua Pu'u Nida traditional house; 2). To explore the ethnomathematical concepts contained in the Nua Pu'u Nida Traditional House. This type of research is exploratory research using an ethnographic approach with taxonomic analysis. The subjects in this study were four people and the researchers themselves. The instruments used are observation sheets, interview guidelines, and documentation. Data analysis used is a triangulation of data sources from researchers, namely by means of documentation and observation and is strengthened by reference books. The results of this study indicate the existence of geometric shapes in the traditional house of Keda Nida. The geometric shapes found are: 1) trapezoidal roof; 2) beam-shaped bearings; 3) a line-shaped roof pole; 4) the roof to the side is triangular in shape; 5) the meeting between two logs that form a corner. The shape of the parts of the traditional house can change the paradigm of students and the community under mathematics which is closely related to daily activities with culture.